2013
DOI: 10.1128/aac.00558-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of the Analysis of Linezolid and Clarithromycin in Oral Fluid of Patients with Multidrug-Resistant Tuberculosis

Abstract: dLinezolid plays an increasingly important role in the treatment of multidrug-resistant tuberculosis (MDR-TB). However, patients should be carefully monitored due to time-and dose-dependent toxicity. Clarithromycin plays a more modest role. Therapeutic drug monitoring may contribute to assessment of treatment regimens, helping to reduce toxicity while maintaining adequate drug exposure. Oral fluid sampling could provide a welcome alternative in cases where conventional plasma sampling is not possible or desira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…HPLC methods have been published for linezolid TDM in plasma [ 128 , 130 ], dried plasma spots [ 131 , 132 ] and oral fluid [ 133 ] with good correlations between methods.…”
Section: Reviewmentioning
confidence: 99%
“…HPLC methods have been published for linezolid TDM in plasma [ 128 , 130 ], dried plasma spots [ 131 , 132 ] and oral fluid [ 133 ] with good correlations between methods.…”
Section: Reviewmentioning
confidence: 99%
“…Table shows the changes in the plasma and saliva levels of LZD at 3, 7 and 12 h after intake. These results were quite similar to the results of Bolhuis et al (). However, the difference between each plasma and saliva level at 3 h was slightly larger than that at 12 h. This result suggests that the trough level of saliva is useful for LZD monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bolhuis et al . () reported that the LZD concentration in serum correlated well with that in saliva at steady state. Hence, we developed a practical analytical HPLC method for the determination of LZD in plasma and saliva.…”
Section: Introductionmentioning
confidence: 97%
“…As there are many other determinants of the salivary drug concentration, such as salivary flow rate, stability of the drug and its metabolites, time of sample collection and ingestion of food or beverages [52], target concentrations in saliva should be established on a drug-to-drug basis [43]. Saliva methods using LC-MS/MS have been published for a few anti-infective drugs (doxycycline, fluconazole, linezolid, lopinavir and oseltamivir) [52][53][54].…”
Section: Outpatient Monitoringmentioning
confidence: 99%